The economics of Canadian immigration levels - Matthew Doyle; Mikal Skuterud; Christopher Worswick (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2023)
In the hope of addressing chronic labour shortages and sluggish economic growth, the Canadian government plans to increase immigration in the coming years to per capita levels not reached since the 1920s. We argue that economic immigration in the Canadian context should aim to boost GDP per capita in the full population including the newcomers. We then examine the potential for increases in Canadian immigration levels to achieve this objective. Our analysis suggests that Canada is not well-positioned to leverage heightened immigration to boost GDP per capita owing primarily to weak capital investment and quantity-quality tradeoffs in immigrant selection. We conclude by providing a framework for identifying the optimal level of economic immigration.
Keywords: J61; F22; J24; 330; Immigration; economic growth; human capital